2023
DOI: 10.3390/neurolint15040093
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Coagulation Disorders and Ischemic Stroke: How to Reconcile Both?

Pietro Crispino

Abstract: Coagulation and fibrinolytic system disorders are conditions in which the blood’s ability to clot is impaired, resulting in an increased risk of thrombosis or bleeding. Although these disorders are the expression of two opposing tendencies, they can often be associated with or be a consequence of each other, contributing to making the prognosis of acute cerebrovascular events more difficult. It is important to recognize those conditions that are characterized by dual alterations in the coagulation and fibrinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 151 publications
0
1
0
Order By: Relevance
“…Research by Jialal et al [ 20 ] demonstrated a significant correlation between the PHR and elevated triglycerides and coagulation factors, suggesting that an elevated PHR may reflect an imbalance in coagulation homeostasis. Ischemic stroke patients often exhibit coagulation abnormalities, with post-stroke complications frequently related to coagulation dysfunction [ 44 ]. In the current study, the PHR showed a linear positive correlation with cardiovascular-specific mortality among stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Jialal et al [ 20 ] demonstrated a significant correlation between the PHR and elevated triglycerides and coagulation factors, suggesting that an elevated PHR may reflect an imbalance in coagulation homeostasis. Ischemic stroke patients often exhibit coagulation abnormalities, with post-stroke complications frequently related to coagulation dysfunction [ 44 ]. In the current study, the PHR showed a linear positive correlation with cardiovascular-specific mortality among stroke survivors.…”
Section: Discussionmentioning
confidence: 99%